From Campus to Community: The Ramadan Spirit of Yannas Husada Pharmacy Academy Students in A Sharing Action - Wibowo, Teguh Setiawan; Adi Febrianti, Ayu Putri; Arum, Azzahroh; Rofiki, Ach. (Jurnal Pengabdian West Science, 2025)
The holy month of Ramadan is a special moment for Islams to enhance social awareness and share with others. Students of the Yannas Husada Pharmacy Academy in Bangkalan contribute to the spirit of giving through a free takjil distribution program for the community. This activity aims to strengthen the relationship between students and society while instilling social values and a sense of care within the academic environment. The implementation method involves active student participation in fundraising, takjil preparation, and distribution to those in need, such as informal workers, road users, and local residents near the campus. In addition to distributing takjil, this initiative is integrated with health education on maintaining a healthy diet during fasting, in alignment with the students’ pharmaceutical knowledge. The results of this activity show high enthusiasm from both students and beneficiaries. The takjil distribution is not merely a social act but also serves as a learning medium for students to apply humanitarian values and professionalism in the healthcare field. This program is expected to raise collective awareness of the importance of sharing and strengthen the role of academics in community service.